The Influence of Promotion Through Social Media on Purchasing Decisions Mediated By Consumer Buying Interest In Malang City - Melinda Yunita Sari; Marsudi Marsudi; Sri Nastiti Andharini (Jurnal Manajemen Bisnis dan Kewirausahaan (JAMANIKA), 2022)
The research was conducted with the aim of obtaining knowledge about the influence of promotions on purchasing decisions for Wardah Products. Using a sample of one hundred respondents. The questionnaire was used as a data collection technique. Scale range analysis and path analysis were used as data analysis techniques. The research conducted has the result that promotion through social media has a positive and significant influence on purchasing decisions. Then promotion through social media has a positive and significant influence on buying interest. Promotions have an influence on purchasing decisions through buying interest variables with the presence of direct and indirect effects, meaning that promotions on purchasing decisions will have a greater influence if buying interest is used.